Ability of single-breath nitrogen closing volume to detect early airway obstruction. Issue 2 (April 1975) - Funahashi, A; Melville, G N; Hamilton, L H
Abstract : In order to determine the ability of single-breath nitrogen closing volume (CV) to detect early airway obstruction, the CV was measured in patients with either minimal obstruction of spirometry or with increased residual volume (RV). A total of 39 subjects was included in this study. The mean CV was largest in patients who had reduced maximum mid-expiratory flow rates (MMF). There was no difference in mean CV between smokers and the patients who had large RV but no airway obstruction, although both groups had higher mean CV than ex-smokers. Normal CV was seen in four of 11 patients who had reduced MMF and in four of seven who had large RV but no airway obstruction. All ex-smokers had normal CV while five of 12 smokers had adnormal CV. The results indicate that the closing volume should be used to complement spirometry, rather than to replace it, for screening of early airway obstruction.